Pregnancy in rudimentary horn of unicornuate uterus: a rare case - Gawandi, Prabhakar S.; Sathe, Vijaysinh P.; Barkase, Akanksha A.; Salunke, Chetana U.; Gaikwad, Priyanka; Patil, Shivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Congenital malformations of the female genital tract result from embryological maldevelopment of Mullerian or paramesonephric ducts. Mullerian duct anomalies (MDAs) are due to agenesis, defective fusion or resorption during embryological development. Unicornuate uterus results due to defective lateral fusion of Mullerian duct. This report discussed a case of pregnancy in rudimentary horn of unicornuate uterus which resulted in rupture of the horn. A patient 35 year old G2A1 with spontaneous conception with 4 months pregnancy came to emergency room with complaints of pain in abdomen and giddiness. On examination her general condition was moderate with pulse rate of 128 bpm, blood pressure of 90/60 mmHg, pallor was present. On per abdomen examination guarding, rigidity and diffuse tenderness was present. On per vaginum examination, uterus size could not be appreciated. Her haemoglobin level was 6 gm%. Ultrasonography of abdomen showed presence of unicornuate uterus with ruptured right horn with fetus in the abdominal cavity and presence of hemoperitoneum. Immediate resuscitative measures were performed, blood transfusion was started and simultaneously patient was shifted to operation theatre for exploratory laparotomy. Intraoperatively hemoperitoneum with unicornuate uterus with non communicating ruptured accessory horn on right side was present and foetus in peritoneal cavity was seen. Ruptured horn was excised and uterus was repaired. The accessory horn and foetus were sent for histopathology examination which was suggestive of placenta increta with gestational hypertrophy and hyperplasia of myometrium with normal tube and ovary. Patient tolerated the procedure well.